Exploring the Relationship Between Pornography Addiction and Religiosity - Prabowo, Dito Aryo (Tazkiya Journal of Psychology, 2022)
Indonesia has recorded reports of complaints in 2020 regarding pornography and cybercrimes that continued to increase from 2011 to 2018. Despite the prevalence, objective approaches to construct, assess, and treat problematic pornography consumption are still unclear due to highly different concepts. This study aims to explore the relationship between pornography addiction and religiosity. Religiosity might be used as a buffer to pornography addiction. However, individuals who engage in pornography consumption with high religious beliefs and religious experiences may perceive their behavior as addictive, hence facilitating them to be more vulnerable to pornography addiction. 1500 online responses from Indonesian citizens to the newly developed Pornography Addiction Scale Indonesia (PASI) and the Centrality of Religiosity Scale (CRS) were obtained using the non-probability sampling technique. There is no significant correlation found between both variables, albeit significant correlations were found in their aspects, namely salience and religious experience; mood modification and religious experience; internal conflict and intellectual; and internal conflict and ideology. Significant mean differences also found between religiosity score and pornography consumption demographic data. The results were discussed using comparison with other findings in other studies.